Audit firm rotation and audit quality: Comparison before vs after the elimination of audit firm rotation regulations in Indonesia - Inas Aisyah Widyaningsih; Iman Harymawan; Agus Widodo Mardijuwono; Eka Sari Ayuningtyas; Dyah Ayu Larasati (Cogent Business & Management, 2019)
This paper examines whether the changes in audit rotation policy affect the relationship between audit firm rotation and audit quality in Indonesia. This study uses 2,403 observations from 371 firms listed on the IDX for the period 2010-2017. This study uses Ordinary Least Squares regression to test the hypothesis. We find that, in the mandatory audit rotation period (pre-period), there is no significant association between audit rotation and audit quality. Interestingly, we find a positive relationship between audit rotation and audit quality in the voluntary audit rotation (post-period). Our result implies that voluntary audit rotation without any coercive regulation is more effective in improving audit quality. This research provides an insight to policy makers that eliminating the regulation of audit firm rotation is an effective decision to enhance audit quality.
Keywords: 650; audit; audit firm rotation; audit quality